Design and development of solar dryer for food preservation (Bangladesh Journal of Scientific and Industrial Research, 2019)
Solar thermal energy is an alternative source of energy which can be used for drying vegetables, fishes, fruits or other kinds of material, such as wood. In Bangladesh, there exist significant post-harvest losses of agricultural products due to lack of the use of proper preservation system. Drying by using solar thermal energy can be an effective solution for this loss. As Bangladesh is situated in latitude 23°43’N and longitude 90°26’E, this is very much suitable to use solar thermal energy. To reduce the limitations of the natural sun drying e.g. exposure of the foodstuff to rain and dust; uncontrolled drying; exposure to direct sunlight; infestation by insects etc., two types of solar dryer (low cost solar dryer for small production and solar dryer for large production) were developed. The design was based on the geographical location of Dhaka, Bangladesh. The experiments were conducted to dry vegetables and fishes. The obtained results revealed that the temperatures inside the dryer were much higher than the ambient temperature. The rapid rate of drying proves its ability to dry food to keep in safe moisture level in a hygienic environment. Microbiological and nutritional values ensure a superior quality of the dried product also.Bangladesh J. Sci. Ind. Res.54(2), 155-160, 2019